Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Governance mechanisms for collective energy decisions in homeowner associations: a two-stage delegation-consensus model - Xinyi Mu; Dujuan Yang; Qi Han (Energy and Buildings, 2026)

Spatiotemporal predictive modeling for coastal phytoplankton based on the Tapnet model: A case study in Zhejiang, China - Yan Wei; Haibin Han; Qinglin Mu; Haodi Zhu; Yueyi Qiao; Shaojian Yang; Chaoyi Yu; Na Wei; Hanyan Luo; Luyuan Zhao; Xuping Zhuo; Yufan Yuan; et al. (Marine Pollution Bulletin, 2026)

The environmental fate of perfluoroalkyl acids in East China Sea sediments: Influence of depositional settings and sediment transport processes - Mingzhi Liu; Zhongyong Yan; Ningning Zhu; Fan Yang; Guoquan Wang; Xiaohua Wang; Qinglin Mu; Oliver A.H. Jones; Xibin Han; Chunfang Zhang (Water Research, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Variable silicate weathering and enhanced reverse weathering during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; Denglin Han; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chun-Yao Liu; Ke Xu; Can Chen; Mu Liu; Daizhao Chen (Geochimica et Cosmochimica Acta, 2026)

Comparison of nitrogen oxides (NO, NO2) analyzers from controlled conditions in a 100 m3 outdoor simulation chamber to field observations - Xuanming Huang; Xiaowei He; Jinzhao Tong; Baobin Han; Shichuan Ni; Zhiwei He; Xuelian Zhong; Xinmiao Xu; Min Cai; Yang Wang; Chenyang Xue; Wenya Niu; et al. (Journal of Environmental Sciences, 2026)

Effects of Second-Order Wave Forces on the Extreme Response Estimation of the TLP Offshore Wind Turbine Under Multi-Directional Wind-Wave Loads - Jiahao Mu; Wei Shi; Linyang Cao; Jinghong Shang; Xu Han; Yang Yang; Liang Liu; Guangyuan Cheng (Journal of Marine Science and Engineering, 2026)
As offshore wind energy advances into deeper waters, the dynamic response and safety assessment of tension leg platform (TLP) wind turbines under complex marine conditions have become focal research points. This study investigates a 15 MW TLP wind turbine, acquiring data on motion responses, mooring tensions, and tower-base loads through time-domain analysis, with extreme value estimation conducted using the mean up-crossing rate method. The results indicate that under normal operating conditions, second-order wave forces significantly influence extreme response estimation. At an exceedance probability of 0.01, the second-order sum-frequency force increases the extreme tower base shear by 4.28% and the bending moment by 10.11% compared to the first-order-only case, while the difference-frequency force has a minor effect. Different wind-wave incidence angles cause distinct variations in turbine motion, with head-on incidence exciting the largest wave-frequency responses and lateral incidence producing relatively weaker excitation effects. Furthermore, the coupling effect between incident direction and second-order wave forces further amplifies extreme response risks. Therefore, it is essential to fully assess the prevailing wind-wave directions in the target sea area and consider the effects of second-order wave forces, especially the sum-frequency component, to ensure the long-term safe operation of TLP wind turbines under complex sea conditions.

Intercalation-mediated bionic nano-hydrogel adhesives for robust omni-domain adhesion - Jialve Sun; Zhengzhi Mu; Tianye Yang; Hexuan Yu; Wenda Song; Zhiyan Zhang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Seawater pH fluctuations during the Ordovician to Silurian transition: Insights from δ11B records in carbonates - Xiangrong Yang; Shaojie Li; Detian Yan; Yue Cai; Denglin Han; Ke Xu; Yanqing Li; Can Chen; Peng Sun; Mu Liu; Chunyao Liu; Daizhao Chen (Global and Planetary Change, 2026)

The moon's formation time recorded in lunar mare basalts - Mu-Han Yang; Qian W.L. Zhang; Richard W. Carlson; Bi-Wen Wang; Dongjian Ouyang; Qiu-Li Li (Icarus, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Cross-phenological domain adaptation for early-stage peach detection - Qiang Zhai; Jingsha Shi; Yi Li; Ziqi Yang; Yaolin Han; Jiong Mu (Computers and Electronics in Agriculture, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Exploring the interaction between vermicompost application and soil types on the dispersal of antibiotic resistome above- and belowground - Meirui Mu; Keqiang Zhang; Ming Yang; Bingjun Han; Yutao Sun; Fengxia Yang (Applied Soil Ecology, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

Isotopic signaling and environmental significance of cave waters in a heavily rocky desertification area - Ju Ni; Yurong Mu; Dayun Zhu; Jialu Wang; Yurong Han; Yingshan Zhao; Ning Yang; Juanfang Du (Applied Geochemistry, 2025)

Multidirectional energy absorption of bionic multi-cell tubes inspired by bamboo phloem - Shuang Zhang; Wenda Song; Zhengzhi Mu; Zhiyan Zhang; Jingde Yang; Hexuan Yu; Wenzheng Wu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Modes of occurrence of rare earth elements and yttrium in bituminous coals with different ranks from the Hedong Coalfield, northern China - Zhenyu Xu; Xiaomei Wang; Fan Deng; Xingxing Guo; Yuxuan Han; Ke Sheng; Yuanhe Mu; Qin Yang (International Journal of Coal Geology, 2025)

Significant effects of earthworm species on antibiotic resistome in livestock manure as revealed by metagenomic analysis - Ming Yang; Liang Peng; Meirui Mu; Fengxia Yang; Zhonghan Li; Bingjun Han; Keqiang Zhang (Environmental Pollution, 2025)

Quasi-Solid-State Electrolytes: Bridging the gap between solid and liquid electrolytes for zinc-ion batteries - Tao Xue; Jinpeng Guan; Yongbiao Mu; Meisheng Han; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Numerical investigation on a quaternary-driven rotary energy recovery device for desalination system: Performance evaluation and theoretical validation - Jie Zhou; Han Qi; Ziyu Wen; Qinghong Zhang; Naitao Yang; Shichen Mu (Desalination, 2025)

Preparation of agriculture film from cow manure for silage maize planting: Experimental study and life cycle assessment - Zixi Han; Xu Zhao; Bingxin Tong; Yongsong Mu; Xiangjun Yang; Yong Hou; Zhiping Zhu (Waste Management, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Analysis of relationship between mixed heavy metal exposure and early renal damage based on a weighted quantile sum regression and Bayesian kernel machine regression model - Qi An; Qingyao Wang; Rujie Liu; Jiachen Zhang; Shuangjing Li; Weitong Shen; Han Zhou; Yufen Liang; Yang Li; Lina Mu; Lijian Lei (Journal of Trace Elements in Medicine and Biology, 2024)

Vermicompost: In situ retardant of antibiotic resistome accumulation in cropland soils - Meirui Mu; Fengxia Yang; Bingjun Han; Guisheng Tian; Keqiang Zhang (Journal of Environmental Sciences, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Berberine alleviated contrast-induced acute kidney injury by mitophagy-mediated NLRP3 inflammasome inactivation in a mice model - Yalin Yang; Shuang Jiang; Yu Mu; Chilu Liu; Yanxing Han; Jiandong Jiang; Yuhong Wang (Toxicology and Applied Pharmacology, 2024)

Critical taste substances and regulatory pathways of fresh lotus seed pulps at different ripeness stages - Yinai Yang; Ruiling Liu; Yanchao Han; Weijie Wu; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2023)

Enhanced biological phosphorus removal by high concentration powder carrier bio-fluidized bed (HPB): Phosphorus distribution, cyclone separation, and metagenomics - Yanyu Mu; Li Wan; Zixuan Liang; Donghai Yang; Hongbo Han; Jing Yi; Xiaohu Dai (Chemosphere, 2023)

Effects of soil habitat changes on antibiotic resistance genes and related microbiomes in paddy fields - Bingjun Han; Fengxia Yang; Shizhou Shen; Meirui Mu; Keqiang Zhang (Science of The Total Environment, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Biological neutralization of bauxite residue with fermented waste sludge and bio-acid, and the microbial ecological restoration - Dainan Qin; Xiaotong Tan; Xin Zhao; Lulu Qian; Yuanyuan Nie; Xiaolin Pan; Qun Gao; Mu Peng; Yang Liu; Xiaoyu Han (Chemical Engineering Journal, 2023)

Human footprints in the Global South accelerate biomass carbon loss in ecologically sensitive regions - Mengqing Geng; Xuecao Li; Haowei Mu; Guojiang Yu; Li Chai; Zhongwen Yang; Haimeng Liu; Jianxi Huang; Han Liu; Zhengshan Ju (Global Change Biology, 2023)
Human activities have placed significant pressure on the terrestrial biosphere, leading to ecosystem degradation and carbon losses. However, the full impact of these activities on terrestrial biomass carbon remains unexplored. In this study, we examined changes in global human footprint (HFP) and human‐induced aboveground biomass carbon (AGBC) losses from 2000 to 2018. Our findings show an increasing trend in HFP globally, resulting in the conversion of wilderness areas to highly modified regions. These changes have altered global biomes' habitats, particularly in tropical and subtropical regions. We also found accelerated AGBC loss driven by HFP expansion, with a total loss of 19.99 ± 0.196 PgC from 2000 to 2018, especially in tropical regions. Additionally, AGBC is more vulnerable in the Global South than in the Global North. Human activities threaten natural habitats, resulting in increasing AGBC loss even in strictly protected areas. Therefore, scientifically guided planning of future human activities is crucial to protect half of Earth through mitigation and adaptation under future risks of climate change and global urbanization.

Implications of vermicompost on antibiotic resistance in tropical agricultural soils – A study in Hainan Island, China - Meirui Mu; Fengxia Yang; Bingjun Han; Qinfen Li; Yongzhen Ding; Keqiang Zhang (Science of The Total Environment, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Metagenomic analysis to determine the characteristics of antibiotic resistance genes in typical antibiotic-contaminated sediments - Han Yang; Mu Xu; Liqing Wang; Xianyun Wang; Erik Jeppesen; Wei Zhang (Journal of Environmental Sciences, 2023)

Insights into the panorama of antibiotic resistome in cropland soils amended with vermicompost in China - Meirui Mu; Fengxia Yang; Bingjun Han; Yongzhen Ding; Keqiang Zhang (Science of The Total Environment, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Bio-inspired supramolecular metallopeptide hydrogel promotes recovery from cutaneous wound - Yun Li; Xiaoyao Cai; Zhilong Wang; Yu Han; Chunhua Ren; Lijun Yang; Zhongyan Wang; Ganen Mu; Haixue Jia; Jianfeng Liu; Jinjian Liu; Cuihong Yang (Chemical Engineering Journal, 2023)

Astrocyte-derived lactate/NADH alters methamphetamine-induced memory consolidation and retrieval by regulating neuronal synaptic plasticity in the dorsal hippocampus - Xu Tan; Xiaoyu Liu; E Liu; Min Liu; Shouhong Mu; Zhaofang Hang; Weikai Han; Tingting Wang; Yang Zhang; Jing Zhang; Qingwei Yue; Jinhao Sun (Brain Structure and Function, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Lithology identification method based on integrated K-means clustering and meta-object representation - Zhimin Cao; Can Yang; Jian Han; Haiwei Mu; Chuan Wan; Pan Gao (Arabian Journal of Geosciences, 2022)

Tea Polyphenols Improve Down-Regulation of Mitochondrial Functional Gene Expression Induced by Bisphenol A in Zebrafish Ovaries - Xiaoxin Dai; Lijun Qiu; Han Zhang; Chunying Xu; Bo Zhao; Yang Gao; Haidong Li; Yi Mu; Zhangjie Chu (Frontiers in Marine Science, 2022)
The plasticizer bisphenol A, a typical endocrine disrupting chemical, is widely present in the environment. Previous studies demonstrated that exposure to bisphenol A can cause reproductive toxicity, abnormal fertilization, and infertility. However, the mechanisms of low-concentration bisphenol A on the reproductive system and treatment measures have not been fully determined. In this study, we explored the transcriptomic profiles of female zebrafish ovaries. The transcriptomic data revealed that mitochondrial NADH dehydrogenase (mt-Nd) genes were significantly decreased in the bisphenol A-exposed group, while the co-administration of tea polyphenols remarkably elevated the expression of mt-Nd genes. To further explore the expression pattern of the mt-Nd, we analyzed the expression of six mt-Nd genes on different days by qRT-PCR in control, bisphenol A-exposed, and bisphenol A-tea polyphenols ovaries. Here, we found that 0.1 mg/L bisphenol A exposure adversely affects the mitochondrial respiratory chain in ovaries and may lead to reproductive disorders. Finally, our study demonstrated that tea polyphenols play a protective role in ovarian mitochondrial dysfunction in low-concentration bisphenol A-exposed female zebrafish.

Productivity of Leymus chinensis grassland is co-limited by water and nitrogen and resilient to climate change - Yujie Shi; Yunna Ao; Baixin Sun; Johannes M. H. Knops; Jinwei Zhang; Zhihan Guo; Xianming De; Jiayu Han; Yuheng Yang; Xiaoyu Jiang; Chunsheng Mu; Junfeng Wang (Plant and Soil, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

Genome-wide characterization and analysis of the anthocyanin biosynthetic genes in Brassica oleracea - Fengqing Han; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Yumei Liu; Zhansheng Li; Yong Wang; Zhiyuan Fang; Jialei Ji; Honghao Lv (Planta, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Numerical investigation on a grouting mechanism with slurry-rock coupling and shear displacement in a single rough fracture - Wenqiang Mu; Lianchong Li; Tianhong Yang; Guofeng Yu; Yunchun Han (Bulletin of Engineering Geology and the Environment, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

Fine mapping and candidate gene identification of the genic male-sterile gene ms3 in cabbage 51S - Fengqing Han; Kaiwen Yuan; Congcong Kong; Xiaoli Zhang; Limei Yang; Mu Zhuang; Yangyong Zhang; Zhansheng Li; Yong Wang; Zhiyuan Fang; Honghao Lv (Theoretical and Applied Genetics, 2018)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)